Traffic Modeling in Serang City Using the Extended Link Transmission Model - Rachim, Dimas Kukuh Nur; Pratiwi, B.N.; Syafrizal, R.; Toyibah, Toyibah (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2024)
In many countries, traffic problem has increased time by time, it has been caused by the increasing amount of vehicle and the lacking of segment road. For the example, urban traffic problem such as traffic congestion has become a big problem for drivers. This research studied urban traffic modeling using the link transmission model (LTM). The method was proposed is mathematical modeling, including car and bus as the objects of research. The cars and buses data were collected directly by the observers at the intersection that has four links and that are connected each other. The simulation process was obtained for the each link at rush hour period. At the interval 6.30-7.30am the total time spend in the link A, B, C, and D were 45.93h, 28.58h, 37.25h, and 19.91h. At the interval 04.00-05.00pm the total time spend in the link A, B, C, and D were 27.38h, 28.58h, 37.25h, and 19.91h. Based on these results, we might to give an advice to control the duration of traffic lights that controlled traffic flow in the each link. The red traffic light duration of link A at 6.30-730am must be lower than the others so the vehicles at link A will send much better and the TTS will turn down.